Verification of Polarization Matching on the Hologram Recording Plane for the Implementation of an Optimized Digital Hologram Printing System - Hwang, Leehwan; Jeong, Jongho; Go, Cheolyoung; Gentet, Philippe; Kim, Jungho; Kwon, Soonchul; Lee, Seunghyun (Frontiers in Physics, 2022)
Conventional studies on digital hologram printer have mainly been conducted on image generation and reconstruction, such as multi-view image generation method, computer-generated hologram(CGH), and a method of displaying a wave-front for a 3D object[1-3]. However, there should be a criterion to evaluate the quality of the reconstructed image because hologram printer use photosensitive recording interference patterns in holographic material[4-5]. For this reason, the efficiency of the image reconstructed from the hologram is generally measured. However, polarization has an effect on hologram regeneration efficiency because holography uses a laser that generates electromagnetic waves. The hologram recording method is usually to match linear polarization in the same direction. but digital hologram printer composed of complex optical components that causes a phase shifting due to a setup error[6-8]. it will be a problem for resulting in unwanted polarization at the final recording plane. In this paper, we analyzed the possible polarization changes and analyze the optimal polarization matching status using values from hologram results and use them as a study to improve the efficiency of hologram results from holographic printer.